Leading Creativity Through The Web: Public Relations Perspectives - Kartini Kamaruzzaman; Mohd Yahya Mohamed Ariffin; Muhamad Zaki Mustafa; Siti Aishah Mohammad Razi (Universiti Sains Islam Malaysia, 2024)
Communication becomes a crucial element in human daily lives and activities. Same goes for organization in which communication is used to lead them disseminate information and establish relationship through communication. In communication, leading organization and public are two things that complementary to each other. Hence of different medium of communication, there are several elements to encounter in the development of website. Apart from that, by leading creativity through website, it also helps organization engaging with audiences 'perception align with organization objectives. This paper gives public relation views of how an organization may maximize the use of website in term of branding, providing smooth and clear navigation for audience and well as implementing the skills of online persuasion and its process that help to control and monitor the acceptance and perception of public. As a result, this could lead to the formation organization reputation. Another aim of this paper is to highlight the concept of leading aspects in creative way to disseminate information to the public. Thus, public relations practitioners should consider the concept to develop their organization websites.